Indigenous knowledge of poisonous plants from Van Kieu and Pa Ko ethnic groups in Quang Tri province, Vietnam - Chi Mai, Nguyen; My Linh, Tran; Huong Giang, Vu; Van Thanh, Bui; Van Anh, Nguyen Thi; Khac Ban, Ninh (Academia Journal of Biology, 2023)
Poisonous plants are known for toxicity to humans and animals. They comprise a large group of plants in the world. This study aims to collect and systematically document the traditional knowledge of poisonous plants by interviewing Van Kieu and Pa Ko ethnic communities in Quang Tri province. A total of 56 poisonous plant species (27 herbs, 15 shrubs and 14 woody plants) of flowering plants belonging to 26 families and 50 genera were found in the study site. Based on the Recorded Poisonous Plant Proportion (RPPP) values, 25 commonly recorded poisonous plants were selected for analyzing Fidelity Level (FL) and Informants Consensus Factor (ICF). The ICF value of eye irritation, neurologic category, skin irritation, gastrointestinal category and respiratory/cardiovascular category was 0.97, 0.97, 0.96, 0.93 and 0.92, respectively. The most notable species (FL: 100%) in the gastrointestinal category were Ricinus communis L. and Millettia erythrocalyx Gagnep. In the respiratory/cardiovascular category, the most important species (FL: 100%) were Gelsemium elegans (Gardner & Champ.) Benth. and Strychnos vanprukii Craib. The presented results will provide fundamental information for further phytochemical and biological investigation to ascertain the toxic compounds of poisonous plants that may be used for the treatment of appropriate diseases.